2013
DOI: 10.1016/j.ymeth.2013.05.027
|View full text |Cite
|
Sign up to set email alerts
|

A negative selection methodology using a microfluidic platform for the isolation and enumeration of circulating tumor cells

Abstract: Circulating tumor cells (CTCs) exist in the peripheral blood stream of metastatic cancer patients at rates of approximately 1 CTC per billion background cells. In order to capture and analyze this rare cell population, various techniques exist that range from antibody-based surface marker positive selection to methods that use physical properties of CTCs to negatively exclude background cells from a CTC population. However, methods to capture cells for functional downstream analyses are limited due to inaccess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 31 publications
0
35
0
Order By: Relevance
“…Recently, several CTC capture systems have been reported that can use markers other than EpCAM for capture and/or analysis 93 , or that rely on negative selection so that a priori knowledge of the surface expression characteristics of CTCs is not required 94 . For example a microfluidic inertial focusing platform — the iCTC chip (Fig.…”
Section: Highly Efficient Capture and Analysis Of Rare Cancer Cellsmentioning
confidence: 99%
“…Recently, several CTC capture systems have been reported that can use markers other than EpCAM for capture and/or analysis 93 , or that rely on negative selection so that a priori knowledge of the surface expression characteristics of CTCs is not required 94 . For example a microfluidic inertial focusing platform — the iCTC chip (Fig.…”
Section: Highly Efficient Capture and Analysis Of Rare Cancer Cellsmentioning
confidence: 99%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 4 have demonstrated the ability to isolate high purity rare cells for clinical applications. [14][15][16][17][18][19][20][21][22][23][24] However, most of these approaches involve sophisticated microfabrication, excessive lab equipment, long process time and are labor intensive, which limit their practical usage in resource-limited settings.…”
mentioning
confidence: 99%
“…MagSweeper was reported to be able to gently extract live CTCs with high purity from unfixed, unfractionated blood 38,71 . The VerIFAST technique uses magnets to selectively and rapidly move the EpCAM positive cells bound to paramagnetic particles between immiscible liquids, where only the cells bound to immunomagnetic beads can cross between phases to enable rapid isolation of CTCs 48 . VerIFAST avoids the multiple transfer or wash steps required in many other CTC isolation methods, which can cause loss of rare cell populations.…”
Section: Methods: Ctc Isolation Approaches and Molecular Characterizamentioning
confidence: 99%